A comparable efficacy and safety between intracardiac echocardiography and transesophageal echocardiography for percutaneous left atrial appendage occlusion - Zhang, Zhi-Yuan; Li, Feng; Zhang, Jie; Zhang, Lei; Liu, Huan-Huan; Zhao, Ning; Yang, Fan; Kong, Qi; Zhou, Yi-Ting; Qian, Ling-Ling; Wang, Ru-Xing (Frontiers in Cardiovascular Medicine, 2023)
Background: Accumulated clinical studies utilize intracardiac echocardiography (ICE) to guide percutaneous left atrial appendage closure (LAAO), but its procedural success and safety compared to traditional transesophageal echocardiography (TEE) remain elusive. We performed a meta-analysis to compare efficacy and safety between ICE and TEE for LAAO. Methods: Studies were screened with four online databases (including the Cochrane Library, Embase, PubMed, and Web of Science) from their inception to 1 December 2022. We utilized random or fixed-effect model to synthesize the clinical outcomes. Subgroup analysis was performed to screen the potential confounding factors. Results: A total of twenty eligible studies with 3,610 atrial fibrillation patients (1,564 patients for ICE and 2,046 patients for TEE) were enrolled. Compared with TEE group, there was no significant difference in procedural success rate (RR=1.01; 95% CI: 1.00,1.02; P=0.171; I²=0.00%), total procedural time [weighted mean difference (WMD) = -5.58; 95%CI: -15.97, 4.81; P=0.292; I²=96.40%], contrast volume (WMD=-2.61; 95%CI: -12.25, 7.02; P=0.595; I²=84.80%), and fluoroscopic time (WMD=-0.34; 95%CI: −2.09, 1.41; P=0.705; I²=82.80%) in the ICE group. Subgroup analysis revealed ICE showed less contrast use than TEE in the lower proportion paroxysmal atrial fibrillation group and lower proportion hypertension. Conclusion: Our study suggests that ICE may have comparable efficacy and safety compared to TEE for LAAO.